Vulnerability of City Ecology: a Narrative of Female Labors and Informal Workers - Ramdhon, Akhmad (Yayasan Jurnal Perempuan, 2014)
Cities and women have experienced the most vulnerable condition under the premise of economic development specifically those living in poverty. Women working in informal sectors are portrait of vulnerable family in cities where men as breadwinner sometimes unable to fulfill the financial basis. They then have to take the risks of living in slum areas in a prohibited territorial area that unable providing basic needs such as clean water, good air ventilation, sanitation, air circulation, and public or common room. Accumulation of this migration to cities has transformed cities into the most vulnerable place to live for those having no money—gentrification.